The Impact of COVID-19 on “Reconstructive Burnout” Following Mastectomy - Victoria A. Hodkiewicz, BS; Christopher Kujalowicz, BSA, BA; Bianca A. Di Chiaro, MD, MPH; Jeewon Chon, MA; Marina Feffer, MPH; Eleanor Bucholz, MD; Timothy W. King, MD, PhD, MBA (Plastic and Reconstructive Surgery, Global Open)
Background:. Achieving successful breast reconstructive outcomes following mastectomy oftentimes coincides with the completion of a multistep surgical sequence. We hypothesize that the COVID-19 pandemic and subsequent postponement of elective procedures added an additional layer of complexity to this process, contributing to failure to achieve complete reconstruction. Methods:. From January 2018 to January 2022, a retrospective review of all included patients undergoing mastectomy at a single institution, Loyola University Medical Center, was conducted. Reconstructive burnout, a term coined by Halani et al, is defined as either “...no breast mound creation or completion of the breast mound without completion of all major revisions.” Results:. Of the 194 included patients, among univariable models, post-COVID patients were 2.37 times more likely to experience burnout (95% confidence interval [CI]: 1.13–4.98; P = 0.022). Postoperative radiation (P < 0.001), wound dehiscence (P = 0.007), infection (P < 0.001), and complications leading to implant removal and/or autologous flap failure (P < 0.001) were all significantly associated with experiencing burnout. In multivariable models, patients who had postoperative radiation and complications leading to explantation and/or flap failure were 2.88 times (95% CI: 1.33–6.24; P = 0.008) and 5.74 times (95% CI: 2.47–12.12; P < 0.001) more likely to experience burnout, respectively. Conclusions:. Patients who underwent mastectomy during the COVID-19 pandemic were significantly more likely to experience reconstructive burnout, but this was explained by procedural characteristics. Our study further reinforces the increased risk of not completing breast reconstruction in patients who undergo postoperative radiation and/or complications leading to implant explantation and/or autologous flap failure.